ANALISIS PENGARUH HARGA, KUALITAS, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK ONLINE DI APLIKASI SHOPEE - Muhammad Fanhas Ahnaf; Wuryaningsih Dwi Lestari (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to determine the effect of price, quality, and lifestyle on consumer purchasing decisions on online products in the Shopee application. This research uses quantitative methods. The population of this study are consumers who have experience in shopping online through Shopee e-commerce in Surakarta. The sampling technique is purpose sampling. The number of samples for this study was calculated by Malhotra. Through Maholtra's calculation, the minimum sample size needed is 135 respondents. The data source for this research is primary data. The data collection method used in this research is by distributing questionnaires via google form. The data analysis technique of this research is using data analysis software, namely SPSS. The result of this study is that price has a significant effect on purchasing decisions. Product quality is negative and has no effect on purchasing decisions. Lifestyle has a significant effect on purchasing decisions. Keywords: Price, Quality, Lifestyle, Shopee E-commerce.